(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Insomnia is becoming most common in this hectic and stressful life. Sleep is one of the most important aspects of good health, and because of sleeplessness people are facing a lot of physical and mental health problems. Jujube fruit (Ziziphus jujuba) contains nucleotide and flavonoids which help to trigger sleeplessness and it has the ability to calm the mind and it helps to improve and encourage sleep. On the other hand, pumpkin seeds are rich in tryptophan which promotes sleep. They also contain both magnesium and zinc, it has been shown to improve the levels of serotonin in the body which helps to improve sleep.